Exploring the Influence of Financial Literacy and Lifestyle Choices on Fi-nancial Management Practices among Young Workers in Batam City's Urban Landscape - Raya, Syifa Ike (Cebong Journal, 2024)
This study investigates the nuanced interplay between lifestyle choices, financial literacy, and financial management behaviors among young workers in Batam City. The research aims to comprehend how lifestyle preferences and varying levels of financial literacy influence the fi-nancial decision-making processes of this demographic within the dynamic urban landscape. Employing a mixed-methods approach, the study combines quantitative surveys and qualitative interviews to gather comprehensive insights. Quantitative data collected from a purposive sample of young workers reveal correlations and associations between lifestyle factors, financial literacy levels, and financial management behaviors. Concurrently, qualitative narratives delve into the subjective experiences and perceptions, unraveling nuanced insights into the intricacies of life-style influences and financial decision-making. The findings underscore the substantial impact of lifestyle choices on spending patterns and financial behaviors among young workers. Urban living, leisure preferences, and peer influences emerged as influential factors impacting financial management. Furthermore, higher levels of financial literacy demonstrated a positive correlation with prudent financial practices, highlighting its pivotal role in informed decision-making. The implications drawn from these findings advocate for tailored interventions focusing on enhancing financial literacy, integrating practical financial education, and aligning lifestyle choices with long-term financial goals.